Fusion of LSB and DWT biometric watermarking for offline handwritten signature - Cheng-Yaw, Low; Andrew Beng-Jin, Teoh; Connie, Tee (2008)
Biometric watermarking refers to the incorporation of biometrics in watermarking technology. In this paper, we present a novel biometric watermarking scheme to embed handwritten signature invisibly in the host as a notice of legitimate ownership. We propose to adaptively fuse Least Significant Bit (LSB) and Discrete Wavelet Transform (DWT)-based approaches into a unison framework, which to be known as LSB-DWT scheme. The performance of LSB-DWT scheme is validated against simulated frequency and geometric attacks, specifically JPG compression, low pass filtering, median filtering, noise addition, scaling, rotation and cropping through visual inspection, Peak Signal to Noise Ratio (PSNR) and watermark distortion rate. Experiment results prove that LSB-DWT scheme is sufficiently robust even in the presence of deliberate distortions.